A view to a kill: markers for developmentally regulated cell death in plants - Maizel, Alexis (Plant physiology, 2015)
Although paradoxical, the selective killing of cells by programmed cell death ([PCD][1]) is an integral part of life ([Ameisen, 2002][2]). In this issue of Plant Physiology , [Olvera-Carrillo et al. (2015)][3] identify a conserved gene signature of [PCD][1] in plants.